Features of the Development of the Microfinance and Credit Monitoring System in Kyrgyzstan and Ukraine - MURZAIBRAIM, Renat; OSMONBETOVA, Venera; SANSYZBAEVA, Gulimhan; IVASHYNA, Svitlana; IVASHYNA, Oleksandr (Theoretical and Practical Research in Economic Fields; Vol 15 No 2 (2024): TPREF, Volume XV, Issue 2(30), Summer 2024, Special Issue, 2024)
This research paper analyses the differences between banking and microfinance business models in the context of credit monitoring systems and funding sources. The purpose of this research was to show the differences in the context of these components of the activities of banks and microfinance organizations (MFOs) on the examples of Kyrgyzstan and Ukraine. The main research methods used were analysis, forecasting and abstraction. The study emphasized the importance of assessing the creditworthiness of clients, including assessment of their financial performance, credit history and other indicators. It was concluded that such analyses are crucial for financial institutions, as they enable them to assess the risk associated with lending and make informed decisions. The article also reviewed the regulatory framework of Kyrgyzstan in terms of credit monitoring of banks and MFOs, differences in their activities depending on the size of the loan, the financial capacity of the borrower, and the collateral assessment process. Also, an idea was formed about the process of financial monitoring in Ukraine, approaches applied in the country. In the process of comparing the two systems, a conclusion was made about their similarities (peculiarities of regulation, fundamental principles of creditworthiness assessment and risk management), but certain differences related to general approaches to monitoring were also noted. The study allows, based on the studied foreign experience, to increase the efficiency of credit monitoring of financial organizations’ clients. It also generally brings new knowledge for the study of the banking and microfinance sectors.